SARS-CoV-2 mRNA Vaccines Foster Potent Antigen-Specific Germinal Center Responses Associated with Neutralizing Antibody Generation (2020)
ABSTRACT: The deployment of effective vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is critical to eradicate the coronavirus disease 2019 (COVID-19) pandemic. Many licensed vaccines confer protection by inducing long-lived plasma cells (LLPCs) and memory B cells (MBCs), cell types canonically generated during germinal center (GC) reactions. Here, we directly compared two vaccine platforms—mRNA vaccines and a recombinant protein formulated with an MF59-like adjuvant—looking for their abilities to quantitatively and qualitatively shape SARS-CoV-2-specific primary GC responses over time. We demonstrated that a single immunization with SARS-CoV-2 mRNA, but not with the recombinant protein vaccine, elicited potent SARS-CoV-2-specific GC B and T follicular helper (Tfh) cell responses as well as LLPCs and MBCs. Importantly, GC responses strongly correlated with neutralizing antibody production. mRNA vaccines more efficiently induced key regulators of the Tfh cell program and influenced the functional properties of Tfh cells. Overall, this study identifies SARS-CoV-2 mRNA vaccines as strong candidates for promoting robust GC-derived immune responses.